Tackler`s head position relative to the ball carrier is highly correlated with head and neck injuries in rugby - Sobue, S.; Kawasaki, T.; Hasegawa, Y.; Shiota, Y.; Ota, C.; Yoneda, T.; Tahara, S.; Maki, N.; Matsuura, T.; Sekiguchi, M.; Itoigawa, Y.; Tateishi, T.; et al. (British Journal of Sports Medicine, 2018)
Objectives: To characterise the tackler`s head position during one-on-one tackling in rugby and to determine the incidence of head, neck and shoulder injuries through analysis of game videos, injury records and a questionnaire completed by the tacklers themselves.